Analisis Kinerja Keuangan Bank Capital Indonesia Tbk - Renova Febri Adisti; Linda Mauliani (Value : Journal of Management and Business, 2023)
In order to ensure the smooth operation of an organization, it is essential for the organization to carry out a assessment of its performance, one which is related to its financial performance. The outcomes of this assessment will offer an insight into the financial feasibility and health of the bank, utilizing various financial ratios such as solvency, profitability, and liquidity ratios. This research employs a quantitative descriptive approach, involving the collection of financial data reports from Bank Capital Indonesia, Tbk. Spanning from 2020 to 2022. In general, Bank Capital Indonesia, Tbk. Demonstrates a strong solvency position, but it should place greater emphasis on enhancing the stability and sustainability of its financial performance, while also addressing fluctuations in profitability and operational efficiency.